Environmental Management : a core text for O Level and IGCSE - Pallister, John. (New York : Oxford, 2007)
Prepare your students for success and provide a well-rounded learning experience. A focus on critical and analytical thinking skills, increases students' ability to reason from an international perspective. Matched to the latest Cambridge syllabus, this text prepares students for exams and beyond.
Includes index.
Keywords: Environmental management -- Examinations -- Study guides; International General Certificate of Secondary Education -- Examinations -- Study guides